Management of Waqf Land for the Muhammadiyah Association of Gading Rejo Pringsewu Lampung Branch - Wagiyo; Purwanto; Arohman; Dhel Juni Pasya (Institute of Computer Science (IOCS), 2022)
Good Waqf Governance must include; Transparency, Accountability, Responsibility, Independence, and Fairness. Persyarikatan Muhammadiyah has assets that are not equipped with legal proof of ownership, and productivity, as well as risks.The method used in this study is to use a qualitative descriptive method which uses data sources through direct observation and interviews as well as documentation of waqf assets.The Gading Rejo Branch Muhammadiyah Association Asset Management can be said to be good, and for those who are certified and AIW it is greater in percentage terms when compared to the 8 Branches in the Pringswu Regency area; namely waqf land that is certified for a location of 31.25% with an area of ​​22.67%, the Gading Rejo Branch 42.115%, an area of ​​47.01%; Likewise for those with AIW status Location 32.81% with an area of ​​66.55%, for the Gading rejo Branch Location it reaches 57.89%, although in area it is 47.01% </66.55%, whereas for those with the status of a letter of intent, the average is location 5.26% </ 35.94% and area 2% </ 10.78%. Use and productivity are very well managed, waqf land is used for educational, social, economic and religious purposes which benefit the general public by 79%, 84% productive. Thus the risk can be said to be low.